Impact of repeated exposure to CPM on CPM efficiency and pain sensitivity in healthy adults: a randomized controlled trial - Rana, Priyanka; Robinson, Michael E.; Alappattu, Meryl J.; Riley III, Joseph; Lott, Donovan; Bishop, Mark D. (Frontiers in Pain Research, 2025)
Conditioned pain modulation (CPM) is a behavioral measure of diffuse noxious inhibitory control (DNIC), an endogenous central pain modulatory mechanism in which one pain stimulus suppresses the perception of another. CPM efficiency is reduced in individuals with chronic pain and serves as a potential predictor for the development of chronic pain conditions. Current research indicates that CPM, traditionally viewed as a static metric, may exhibit protocol-dependent variability in its effects on pain sensitivity, potentially through neuroplastic mechanisms and central pain processing pathways. This randomized controlled trial (NCT05783362) investigated whether repeated activation of central pain modulatory systems enhances CPM efficiency. The secondary aim examined associations between repeated CPM exposure and pain-related psychological factors. Sixty healthy participants (52% female; ages 18–75) were randomly allocated to High Exposure (HE), Low Exposure (LE), or No Exposure (NE) CPM intervention groups. Pre- and post-intervention measures included CPM efficiency and pain sensitivity across thermal and pressure pain tests. Two-way ANOVA analyses revealed significant main effects for both time (p < 0.001, η2 = 0.23) and intervention (p = 0.030, η2 = 0.107) on CPM efficiency when comparing HE and LE groups from pre- to post-intervention. One-way ANOVA analysis at the final visit showed that HE demonstrated significantly higher CPM efficiency compared to LE (p = 0.02, Cohen's d = 0.73), while comparisons between HE and NE approached but did not reach statistical significance (p = 0.053–0.060; medium-to-large effect sizes, Cohen's d > 0.70). This was supported by increased heat threshold pain intensity ratings (p < 0.001, η2 = 0.13), suggesting broader adaptations in pain processing that strengthen descending pain control mechanisms. Other QST measures and psychological variables remained unchanged, suggesting the specificity of the modulatory enhancement. Results support the plasticity of endogenous pain modulation and suggest potential therapeutic applications for pain management interventions.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT05783362, identifier NCT05783362.